Perancangan Sistem Informasi Penjualan Air Galon Isi Ulang Di Kota Palangka Raya Berbasis Web - Wahyudi, Teguh; Sahay, Abertun Sagit; Sylviana, Felicia (Journal of Information Technology and Computer Science, 2022)
This system was built with the aim of being a medium of sales information for refilling gallon water depots and providing information for people who want to buy refill gallon water. With this system, it is expected to be useful as a medium for expanding information about refill gallon water depots, helping consumers to purchase gallons of refill water easily, and the purchase of refill gallon water can be done without the need for the charging depot location. The methodology used in the manufacture of "Refill Gallons of Water Sales Information Systems Design in the City of Palangka Raya Based on Web" is Waterfall According to Ian Sommerville, the Requirement Analysis and Definition, System and Software Design, Implementation and Unit Testing, Integration and System Testing, and Operation and maintenance. This methodology was chosen because every step of structured development was visualized, and clearly documented. At the analysis stage, data collection and needs analysis were made. At the design stage, Data Flow Diagram (DFD) and Entity Relationship Diagram (ERD) are made. At the implementation stage, the system is made using PHP and Javascript as a programming language, and MySQL as a database server. The test method used is the Blackbox Testing method. Test results using this Blackbox method from the analysis process until the implementation is obtained that the system can carry out data processing such as adding/saving, deleting, changing, and searching. Users can enter data and data can be processed and produce location, product, transaction, and report information. "Refill Gallon Water Sales Information Systems Design in the City of Palangka Raya Based on Web" is able to provide information needed by customers and visitors. In the system there are several features that can be used by the admin, operators, customers and visitors though. So that the functionality of this website is appropriate in accordance with the initial purpose of making the system, "Refill Gallon Water Sales Information Systems Design in the City of Palangka Raya Based on Web " can still be developed again.